Clinical obesity - finally a change of paradigm? From BMI to chronic disease - Sucharda, Petr (Casopis lekaru ceskych, 2025)
The still valid method of defining obesity by the current body mass index (BMI) value does not adequately reflect the severity or health risks of individuals and does not meet the requirements of evidence-based medicine. This definition of obesity has, among other things, led in the past to proposals for such problematic categories as metabolically healthy obesity or obesity with normal weight, and it also contributes to the so-called obesity paradox. The definition of clinical obesity according to The Lancet Diabetes & Endocrinology Commission addresses these shortcomings and characterizes obesity as a chronic, systemic disease characterized by changes in the function of tissues, organs, the whole individual, or their combinations due to excessive fat accumulation. Conditions with increased amounts of fat tissue without such changes are referred to as preclinical obesity; the recommendations for the care of individuals with preclinical obesity are somewhat problematic.
Keywords: obezita; Obesity; Body Mass Index; lidé; Chronic Disease; index tělesné hmotnosti; chronická nemoc; Humans; body mass index, obesity, clinical obesity, preclinical obesity, obesity paradox